Effect of Supplementary Feeding on Weight Gain for Malnourished Toddlers Aged 6-59 Months - Rifqi Firmania Ayunani; Yessy Nur Endah Sary; Tutik Ekasari; Nova Hikmawati (Health and Technology Journal (HTechJ), 2023)
One of the factors that affect a person's level of health is good nutritional status. Providing additional food or nutritional supplementation to malnourished toddlers is one of the treatments to overcome the problem of malnutrition. The purpose of this study was to determine the effect of supplementary feeding on weight gain in malnourished toddlers aged 6-59 months. This study used a pre-experimental design. Data was taken from direct observation sheets on respondents in the Pasirian Public Health Center work area which was carried out from July to August 2022 with a population of 32 respondents and a sample of 21 respondents using purposive sampling. technique. Data collection includes coding, editing, and tabulating. Then the data were analyzed by computer with the help of SPSS. The results showed that in malnourished toddlers who were given additional food, there were 17 respondents who experienced weight gain (81%) and 4 respondents who did not gain weight (19%). Statistical results using the T-test showed a p-value of 0.001. There is an effect of supplementary feeding on weight gain in malnourished toddlers aged 6-59 months at the Pasirian Public Health Center.